2017
DOI: 10.3171/2016.8.focus16112
|View full text |Cite
|
Sign up to set email alerts
|

Bone graft options for spinal fusion following resection of spinal column tumors: systematic review and meta-analysis

Abstract: OBJECTIVE With the advent of new adjunctive therapy, the overall survival of patients harboring spinal column tumors has improved. However, there is limited knowledge regarding the optimal bone graft options following resection of spinal column tumors, due to their relative rarity and because fusion outcomes in this cohort are affected by various factors, such as radiation therapy (RT) and chemotherapy. Furthermore, bone graft options are often limited following tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 77 publications
0
14
0
Order By: Relevance
“…Variable fusion rates in this population are reported (36%-100%) and various options for bone graft are used according to surgeon's preference. 42 (7) Lastly, the authors routinely use intraoperative electrophysiological monitoring, which offers valuable intraoperative knowledge of the integrity of the motor and sensory tracts. 43 There is no level 1 evidence to support the routine use of INM and in case of urgent need of spinal cord decompression; the absence of INM should not delay surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Variable fusion rates in this population are reported (36%-100%) and various options for bone graft are used according to surgeon's preference. 42 (7) Lastly, the authors routinely use intraoperative electrophysiological monitoring, which offers valuable intraoperative knowledge of the integrity of the motor and sensory tracts. 43 There is no level 1 evidence to support the routine use of INM and in case of urgent need of spinal cord decompression; the absence of INM should not delay surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Graft material is matter of debate in cancer surgeries. [51] Fusion mass often suffers from overall poor healing potential, an effect of radiation and chemotherapy. We used only DBM in all cases reported here.…”
Section: Discussionmentioning
confidence: 99%
“…[1718] In general, autologous bone graft should be avoided in cancer surgeries unless the graft material has been treated. [51] Coumans et al . used liquid nitrogen to treat the autologous bone graft before using.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another previous study reported that the time to fusion ranged from 3 to 9 months. 19 Instead of removing the plate at 1 year after the first (primary) surgery, 18 the authors removed the plate at 2 years after the first surgery (at the age of 9 years) to ensure that the fusion had occurred and the C-spine could continue its growth. It is believed that by the time a child reaches 8-10 years of age, the cervical spine reaches adult proportions.…”
Section: Discussionmentioning
confidence: 99%